THE RELATIONSHIP BETWEEN THE ONSET OF SEVERE PREECLAMPSIA AND PERINATAL COMPLICATIONS AT RUMKITAL Dr. RAMELAN IN SURABAYA - Widya Retno; Ivon Diah Wittiarika; Muhammad Aldika Akbar (Indonesian Midwifery and Health Sciences Journal, 2021)
Abstract Background: Preeclampsia is one of the biggest causes of maternal-fetal morbidity and mortality. Based on the prognosis, the classification of Preeclampsia is early onset (<34 weeks) and late onset (> 34 weeks). Purpose: to investigate the relationship between the onset of severe Preeclampsia and perinatal complications. Method: This research is a quantitative study with a retrospective observational analytic study type and collected medical record data. The study population was severe Preeclampsia  patients who gave birth at RUMKITAL Dr. Ramelan Surabaya for the period January 2018 - June 2020 and has no previous history of chronic hypertension. The research sample was 79 subjects with 44 subjects early onset, and 35 subjects late onset. Perinatal complications  examined are preterm delivery, asphyxia, LBW, IUGR, stillbirth. The chi-square test or Fisher’s Exact Test was used to analyze relationships. Result: From the results of the study, the comparison of the percentage from early onset and late onset that experienced complications was 93.2% vs 48.6%, p-value = 0.000, OR = 14.5, CI = 3,764–55,635.  At preterm delivery, it was found that 75% vs 28.6%, p-value = 0.000,  OR = 7.5, CI = 2,754-20,422. . In asphyxia, it was found 41.7% vs 31.4%, p-value = 0.46. At LBW, it was found 72.7% vs 17.1%, p-value = 0,000, OR = 12.9, CI = 4,285-38,771. In IUGR, it was found that 15.9% vs 2.9%, p-value = 0.000. In stillbirth, it was found 18.2% vs 0% and p-value = 0.008. Conclusion: the onset of severe Preeclampsia is related with perinatal complications. Complications associated with the onset severe Preeclampsia are preterm, LBW, stillbirth. Meanwhile, complications that are not related with the onset severe Preeclampsia are asphyxia and IUGR